Assessment of Patients’ Understanding about Prescribed Medications at Outdoor Patient Department of Tertiary Care Hospital in Central Gujarat, India - Bariya, Bhaveshbhai Rameshbhai; Parmar, Rahul J; Mazumdar, Vihang S (Unnes Journal of Public Health, 2021)
Medication is an important part of a patient's treatment by clinicians and is one of the measures taken by them during the entire period of treatment. This descriptive cross-sectional study aims to assess patients’ understanding about prescribed medication obtained after consultation with clinicians at the outdoor patient department of a tertiary care hospital in central Gujarat, India. 184 patients from different clinical departments were interviewed after their consultation with the clinician. Majority of the subjects (45.5%) were 25-44 years of age, while the rest ranged from 45-54 years of age group. Furthermore, 55.5% of the subjects were female, 20.4% were Illiterate people, and 32.5% were educated up to primary level. The results showed that 84.3% of the patients were informed about proposed treatment duration, while 13.9% were informed about diet relation. Therefore, the patients had fair knowledge about the disease they were suffering from and proposed duration of treatment, but they were not aware of about the line of treatment. In conclusion, patients need to be educated about the correct use of medications by clinicians.